THE VALUES OF CHARACTER EDUCATION IN THE PAPPASANG MANDAR TEXT AND ITS IMPLICATIONS FOR MANDAR SOCIETY - Burhanuddin, Burhanuddin; Afiah, Nur; Askarullah, Askarullah (Al-Qalam, 2023)
This research used a qualitative approach to explore character education values in the Pappasang Mandar text. This research method involved an in-depth analysis of various aspects of the characters reflected in the text. The results of data analysis show that Pappasang Mandar consistently contains several fundamental character values, including Respect, Responsibility, Justice, Citizenship, Religious, Honesty, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit, Love of the Motherland, Friendly/Communicative, Love of Peace, Love of Reading, Care for the Environment and Care for the Social. In addition, this research highlights the significant role of Pappasang as a life guide in Mandar society, which is not only considered a text but an integral part of people's daily lives. This text establishes norms that lead to positive values, making it an essential instrument for shaping the behavior and thinking patterns of theMandar community. This implication illustrates that Pappasang is not just a cultural heritage but also a tool that influences and enriches the lives of society. This research contributes to understanding character values in the Mandar cultural context. Its practical implications are relevant in educational curriculum development, emphasizing developing and strengthening students' character. These findings can be a valuable guide for educators and policymakersin designing a holistic curriculum, which does not only focus on academic aspects but also the formation of solid character.